The Effects of Imperata cylindrica Root Extract on Spermatozoa Membrane Integrity Using Hypo-Osmotic Swelling Test - Silvani Permatasari; Febriana Dwi Nanda; Sigit Nurfianto; Septi Handayani; Margaretha Yayu Indah Anugerahny (Majalah Obat Tradisional, 2025)
High levels of reactive oxygen species (ROS) may trigger oxidative stress that harms the structural integrity of the sperm cell membrane. Concerning this case, ethanol extract from the alang-alang (Imperata cylindrica) root is considered capable of maintaining sperm quality. However, tests of spermatozoa membrane integrity in vitro have not been conducted. This research purposed to determine the effects of different concentrations of I. cylindrica root extracts on spermatozoa membrane integrity, analyzed by the hypo-osmotic swelling test. The I. cylindrica root extracts (concentrations of 1000 ng/mL, 2000 ng/mL, 3000 ng/mL, and 4000 ng/mL) were obtained through maceration extraction for 3 × 24 hours with 96% ethanol solvent. GC-MS analysis was then conducted to identify compounds in the extract. The sample used for the membrane integrity test was in vitro human spermatozoa. Priorly, it was washed, mixed with BWW medium, and incubated at 37℃ for 60 minutes with I. cylindrica root extracts and the control group. Furthermore, semen was added to the HOS solution. The yields exhibited that the highest compounds in the ethanol extracts of I. cylindrica root were hexadecanoic acid, palmitic acid, octadec-9-enoic acid, and stearic acid. Further, the spermatozoa membrane integrity increased significantly with the higher concentrations of the I. cylindrica extracts. Moreover, the extracts could maintain the membrane integrity more than the control group, where the most effective result was achieved at 1000 ng/mL I. cylindrica extracts, since its minimum concentration can induce a biological response.